ACE INHIBITORS IN ARTERIAL HYPERTENSION TREATMENT: FOCUS ON LISINOPRIL - V. I. Podzolkov; K. K. Osadchy (Рациональная фармакотерапия в кардиологии)
Approaches to the choice of antihypertensive pharmacotherapy are discussed. Evidence base of ACE inhibitor lisinopril is surveyed. Data about lisinopril effects on different endpoints, organoprotective action and advantages over other ACE inhibitors are presented.